Ekstazi - Lovrečič, Mercedes (Zdravstveno varstvo, 2005)
Ecstasy (E) is the most popular synthetic drug among young people. E users believe in the relative safety of this drug, yet the research literature reports great risk of ecstasy for health. The article summarizes the key epidemiological characteristics of E use, data on illegal production and seizures, effects, with special emphasis on mental complications and consequences. In vulnerable individuals, the use of E can cause life-threatening, and sometimes long-term physical and psychic complications and consequences. The professional literature dealing with mental health emphasises the risk of different kinds of disorders, which can be long-term and treatment resistant. Education of E users is one of preventive activities that can significantly decrease risk behaviour and its consequences in this population.
Keywords: droge; ekstazi; posledice; učinki; zapleti